Use of Self Medicated Antibiotics in the Population of Peelamedu City, Tamil Nadu - Rodrigues, Prudence A; Gayathri, P.S.M.; N, Devaki O.; Abdulla, Nawaf; Shankar, S.L. Ravi; K, Karan; Abimaheshwaran, K. (Journal of Pharmacy Practice and Community Medicine)
Background: One of the major consequences of Self-medication with antibiotics is Antibiotic resistance. Poor community knowledge and attitude towards antibiotic use is a major concern. This study aimed at assessing and improving the knowledge and attitude towards antibiotic use in the community of Peelamedu city, Coimbatore. Methods: A descriptive observational study was conducted in the community population of Peelamedu city, Coimbatore. The study interview was based on an evaluated questionnaire, which included the knowledge, attitude and practice-based questions to assess the SMA use in the community and they were educated on SMA, based on a validated pamphlet, a feedback was obtained. Results were analyzed and concluded. Results: Among the 150 respondents, nearly 60% had moderate knowledge on SMA. The practice of SMA was influenced by education, attitude, previous experience and suggestions from family members and friends. The main source of antibiotics for selfmedication was found to be the community pharmacies. The most common reason cited for taking antibiotics was cold and flu (50.7%) followed by urinary tract infection (14.0%), Eye, ear and GI related infections (8.7%) and the least for dental infections (4%). A positive correlation was noted between the number of family members and the attitude statement about using self-medicated antibiotics for self-healthcare (p value<0.0063). Also there existed a positive correlation between the education provided to the respondents and the knowledge and attitude respectively. Conclusion: The study has generated information on the knowledge, attitude and practice of selfmedication in the community of Peelamedu city, Coimbatore. The study also remarks the essentiality and requirement of public based educational programme to improve their knowledge on SMA and their maleficent effects.
Keywords: Antibiotics; Self medication; Antibiotic resistance; Community Pharmacy; Community awareness